Development and evaluation of mPEG-PLLA polymeric micelles encapsulating enrofloxacin for enhanced solubility, bioavailability, and antibacterial performance - Sun, Yanling; Mao, Yanan; He, Xin; Zhao, Xinghua (Frontiers in Veterinary Science, 2025)
The aim of this study was to prepare polymeric micelles composed of enrofloxacin (ENR) and methoxy poly (ethylene glycol)-poly(lactide) (mPEG-PLLA) using a solvent evaporation method to overcome the solubility-limited oral bioavailability of ENR. The formulation was optimized using a Box–Behnken design (BBD) to obtain ENR polymeric micelles (ENR-m) with high drug loading (DL, %) and entrapment efficiency (EE, %). The physicochemical properties, in vitro drug release, pharmacokinetics, and antibacterial efficacy were evaluated in comparison to pure ENR. ENR-m was successfully prepared and demonstrated satisfactory drug loading (68.38 ± 0.22%), entrapment efficiency (88.40 ± 0.91%), particle size (PS) (133.67 ± 3.10 nm), and polydispersity index (PDI) (0.13 ± 0.03). The ENR-m also exhibited excellent stability under environmental conditions (40°C and 75% relative humidity (RH)). In vitro release of ENR from micelles was accelerated in a PBS solution. A pharmacokinetic study on beagles revealed that the oral bioavailability of ENR-m was enhanced by approximately 1.60-fold compared to pure ENR (p < 0.01) and by 1.66-fold compared to commercially available tablets of ENR (p < 0.01). The antibacterial activity of ENR-m against Escherichia coli (E. coli) and Salmonella typhi (S. typhi) was stronger than that of pure ENR.